Identification of New Tumor-Related Gene Mutations in Chinese Gastrointestinal Stromal Tumors - Feng, Yuyang; Yao, Surui; Pu, Zhening; Cheng, Han; Fei, Bojian; Zou, Jian; Huang, Zhaohui (Frontiers in Cell and Developmental Biology, 2021)
Gastrointestinal stromal tumors (GISTs) are the most common mesenchymal tumors of the gastrointestinal tract. As the main GIST drivers, gain-of-function mutations in KIT or PDGFRA are closely associated with not only tumor development and progression but also therapeutic response. In addition to the status of KIT and PDGFRA, little is known about other potential GIST-related genes. In this study, we identified the mutation profiles in 49 KIT-mutated GIST tumors using the whole exome sequencing (WES) method. Furthermore, some representative mutations were further validated in an independent GIST cohort using the SNaPshot SNP assay. We identified extensive and diverse mutations of KIT in GIST, including many undescribed variants. In addition, we revealed some new tumor-related gene mutations with unknown pathogenicity. By enrichment analyses of gene function and protein-protein interaction network construction, we showed that these genes were enriched in several important cancer- or metabolism-related signaling pathways, including PI3K-AKT,RTK-RAS, Notch, Wnt, Hippo, mTOR, AMPK, and insulin signaling. In particular, DNA repair-related genes, including MLH1, MSH6, BRCA1, BRCA2, and POLE, are frequently mutated in GISTs, suggesting that immune checkpoint blockade may have promising clinical applications for these GIST subpopulations. In conclusion, in addition to extensive and diverse mutations of KIT, some genes related to DNA-repair and cell metabolism may play important roles in the development, progression and therapeutic response of GIST.